Problems found with access to new training facility for Paralympic athletes (The Mainichi, 2018)
The second National Training Center (NTC) mainly designed for use by Paralympic athletes is due to open in June 2019 in the capital's Kita Ward. However problems not with the facility itself, but the route to get there, have arisen....